Respuesta :

Answer:

Step-by-step explanation:

If base of variable is same, add the powers

1) x² * x * x³ * x⁵ = x²⁺¹⁺³⁺⁵ = x¹¹

2) -2n² * -n⁴ * 5n³ = (-2* -1*  5 ) *n²⁺⁴⁺³ = 10n⁹

3)-3x⁴ * 2x⁵ * - x = (-3 * 2 * -1)* x⁵⁺⁴⁺¹ = 6x¹⁰

Answer:

1. [tex]x^{11}[/tex]     2. 10[tex]n^{9}[/tex]   3.  6[tex]x^{10}[/tex]

Step-by-step explanation:

1.   [tex]x^{11}[/tex]

Imagine the expression is written like this:

(x)(x) *  (x)  * (x)(x)(x) * (x)(x)(x)(x)(x)

Simply add up the number of x's and have that number be the exponent.

There are 11 x's, so it will be [tex]x^{11}[/tex]

2. 10[tex]n^{9}[/tex]

Do the same as above, but this time remember that two negatives equal a positive.

10[tex]n^{9}[/tex]

3. 6[tex]x^{10}[/tex]

Again, two negatives equal a positive.

-3 x 2 x -1 = 6

Do the same as the above two.

6[tex]x^{10}[/tex]

ACCESS MORE